The Impact of Organizational Psychology Factors for the Cross-Border Legal Service Entrepreneurs - Xu, Chengjin; Zhang, Zhe (Frontiers in Psychology, 2020)
Trade friction has always been a prominent feature in the current economic development of the world. Its impacts on multinational enterprises are self-evident, but its psychological effects on the multinational entrepreneurs are still unclear. In order to understand the impacts of trade friction on psychological effects of multinational legal service entrepreneurs, 305 multinational entrepreneurs were selected in this study for questionnaire survey, and Spearman’s correlation and regression models were used to analyze the correlation among economic pressure, the thought of recession, self-efficacy, and social support. The structural equation model was used to analyze the influence path of economic pressure and social support on the thought of entrepreneurial recession, as well as the influence path of multinational entrepreneurship orientation and value-chain potential on the international performance. The results show that economic pressure is significantly and positively correlated with the thought of recession and self-efficacy extremely and significantly and negatively correlated with objective support and support utilization extremely; social support will reverse the thought of entrepreneurial recession caused by the economic pressure; the indirect impact path coefficient of social support utilization in economic pressure and entrepreneurial recession is – 0.281; the indirect impact path coefficient of value-chain potential in multinational entrepreneurial motivation and international performance is – 0.424. It shows that trade friction will indirectly trigger the thought of entrepreneurial recession of entrepreneurs by reducing their economic incomes. Besides, the social support utilization can significantly regulate the relationship between the economic pressure and the thought of entrepreneurial recession. Therefore, the value-chain potential plays an intermediary role in multinational entrepreneurial motivation and international performance.